Family Education in The Book 'UqÅ«d Al-Lujjain fá¿™ Bayani HuqÅ«qi Al-Zaujain - Imam Tabroni; Jajang Dodi (Muttaqien Publishing, Lembaga Penelitian dan Pengabdian kepada Mayarakat (P3M) STAI DR. KH.EZ. Muttaqien Purwakarta, 2022)
Building a family that is calm, harmonious, and full of love or in accordance with the guidance of the al-Qur'an and the Sunnah of the Prophet Muhammad is a dream for every Muslim married couple in a household. The family always adheres to the teachings of Islam to navigate the essential life. The purpose of this research is to find out the concept of education in the family in an Islamic way through the work of the thoughts of Nawawi in the book 'Uqud Al Lujjayn Fiy Bayaani Huquuqi Al Zaujayyn, related to its relevance to the concept of education in families at this time. The purpose of this research is to find out the concept of education in the family in an Islamic way through the work of the thoughts of Syeikh Nawawi Al-Bantani in the book 'Uqud Al Lujjayn Fiy Bayaani Huquuqi Al Zaujayyn, related to its relevance to the concept of education in families at this time. The results of his research, the concept of Islamic education in the family by the thought of Syeikh Nawawi Al-Bantani in the book â€œUqud Al Lujjayn Fiy Bayaani Huquuqi Al Zaujayynâ€ is still very relevant as a reference for education in the family at this time, in order to create a sakinah family, mawaddah, warahmah, in accordance with the guidance of the al-Qur'an and the Sunnah of the Prophet Muhammad. Syeikh Nawawi Al-Bantani's paradigm of thought which is spiritual, traditional, Sufistic with his distinctive belief in text sources (Al-Quran and Hadith) and non-text (large figures or scholars) according to Ahlu Sunnah Wal Jama'ah's understanding makes it unique, in the middle. the emergence of reformers and reformers of Islamic teachings in his time.